Endoparasitic Infestation of the Nile Squeaker, Synodontis schall (Bloch and Schneider, 1801) from the Cross River Estuary, Nigeria - Effanga, Emmanuel Offiong; Eyo, Victor Oscar (Asian Journal of Advances in Agricultural Research, 2018)
The mean goal of this study was to determine the abundance, intensity, and prevalence of endoparasites of Synodontis schall from the Cross River Estuary, Nigeria, and the public health implications to fish consumers. A total of 150 fresh samples were collected between May and October 2013 from the catches of the artisanal fisheries at Nsidung beach and transported to the Fisheries and Aquaculture laboratory, University of Calabar, for identification and parasitological examination. The internal organs including intestines and stomach were removed and examined microscopically for parasites. The overall prevalence of endoparasites was 11.33% and endoparasites recovered belonged to nematode (Camallanus kirandensi), Cestode (Diphyllobothrium sp. and Proteocephalus largoproglotis), and Acanthocephalans (Pomporhynchus laevis and Acanthela sp.). Parasites were more prevalent in the intestine (28 endoparasites – 59.57%) than the stomach (19 endoparasites – 40.43%) indicating that the intestine is a more favorable internal organ for endoparasites. Infestation rate was significantly higher (P<0.05) in 10 – 14.9 cm size class (53.33%), followed by 15 – 19.9cm (3.00%), followed by ≥ 20.0 cm (8.00%) and lowest in 5-9.9 cm size class (4.67%). Prevalence and abundance was significantly higher (P<0.05) in 15 – 19.9 cm size class, followed by 20 – 24.9 cm, followed by 10 -14.9 cm and lowest in 5 – 9.9 cm while intensity was highest in 10 – 14.9 cm size class, followed by 15 – 19.9 cm, followed by ≥ 20.0 cm and lowest in 5 – 9.9 cm. Intensity and abundance of endoparasites were significantly higher (P<0.05) in females than males whereas prevalence was higher in males than females. It can be concluded that the risk of zoonosis was extremely low because intestine and stomach of this fish were not consumed. However, to eliminate the risk of zoonosis, fish consumed should be previously washed with clean water and cooked properly.
Keywords: Endoparasites; abundance; intensity; prevalence; Synodontis schall; Cross River Estuary